Behawioryzm i konstruktywizm wobec człowieczych czynów, wiedzy i moralności …ku (nie)podzielanej edukacji - Stanisław Dylak (Problemy Wczesnej Edukacji)
As we delve deeper into the roots of knowledge, we discover more and more relationships between its particular spheres, and also its descriptions or interpretations. This prompts a search for shared, interdisciplinary areas. Furthermore, what is theoretical is easier to divide into particular spheres than what is practical. The paper undertakes an attempt to seek shared areas for education under constructivism and behaviourism, in issues which appear key to education and concerning knowledge, morality and human practical acts.